The (in)efficiency of trams and buses in Brussels: a fine geographical analysis - Xavier Courtois (Brussels Studies, 2008)
At a time when mobility in Brussels is becoming increasingly critical from the standpoints of the environment and efficiency, this article gives a detailed and exhaustive analysis of the geography of traffic conditions affecting the trams and buses of Brussels’ main mass transit network. The finely disaggregated data that we were able to obtain from the Brussels Interborough Transport Company (STIB/MIVB) enabled us to calculate and map three indicators (commercial speed, irregularity, and lost time) that make it possible to identify the network’s problem spots. The figures show that, in the current state of affairs, fewer than a third of the city’s tram line segments meet the commercial speed performance levels that they are expected to achieve under STIB/ MIVB’s new management contract. The problem spots, which are found primarily but not solely in the first urban ring (from Saint-Gilles to Schaerbeek, via Ixelles), stem basically from a mixture of roads and public areas that are narrow and/or heavily used by cars, inappropriate traffic light management, and political stalemates that make it impossible to get around the first three factors. In this framework, the regional mobility and sustainable development plans can scarcely be achieved.